Effects of Footwear on Impact Forces and Soft Tissue Vibrations during Drop Jumps and Unanticipated Drop Landings - Fu, W.; Liu, Y.; Zhang, S. (International Journal of Sports Medicine, 2013)
The purpose of this study was to explore the footwear effects on impact forces and soft-tissue vibrations during landing. 12 male basketball players were instructed to perform drop jumps and unanticipated drop landings from 30 cm, 45 cm, and 60 cm heights in basketball shoes (BS) and control shoes (CS). 3D kinematics, ground reaction force (GRF), and soft-tissue vibrations of the leg, and acceleration of the shoe heel counter were measured simultaneously. The results showed no significant shoe effect on the characteristics of the impact force nor on the resonance frequency and peak transmissibility of soft-tissue vibrations during the impact phase of the drop jump. For the unanticipated drop landings, however, the magnitude of both peak GRF and peak loading rate were significantly lower with BS compared to CS across all 3 heights (p<0.05); meanwhile BS showed a significant decrease in GRF frequency compared to CS at 45 cm (p<0.05) and 60 cm (p<0.01) heights. Furthermore, the peak transmissibility in BS was significantly lower than that in CS for both the quadriceps and hamstrings during the 60 cm unanticipated drop landing (p<0.05). These findings provide preliminary evidence suggesting that if the neuromuscular system fails to prepare properly for an impact during landing, a shoe intervention may be an effective method for minimizing impact force and reducing soft tissue resonance.
Keywords: footwear; impact forces; soft tissue vibrations; landings